2022
DOI: 10.1101/2022.10.25.513732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic manipulation of Gq- and Gi/o-coupled receptor signaling in neurons and heart muscle cells

Abstract: G protein-coupled receptors (GPCRs) transmit extracellular signals into the cell depending on the type of G protein. To analyze the functions of GPCR signaling, we developed optogenetic tools using animal G protein-coupled bistable rhodopsins that can be controlled into active and inactive states by light irradiation. We expressed Gq- and Gi/o-coupled bistable rhodopsins in hindbrain reticulospinal V2a neurons, which are involved in locomotion, or in cardiomyocytes of zebrafish. Light stimulation of the reticu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Bistable opsins are promising for optogenetic applications because they can be activated and inactivated with specific wavelengths of light, providing high temporal precision. For instance, JSR1 has been used as an optogenetic tool in zebrafish reticulospinal V2a neurons, where activation of JSR1 lead to an increase of Ca 2+ and evoked a change in swimming behaviour [44]. The main issue with using JSR1 as an optogenetic tool is that the λ max of the active and inactive states overlap, meaning that there will be a mixture of active and inactive states upon illumination and the activity of JSR1 cannot be controlled precisely [16].…”
Section: Discussionmentioning
confidence: 99%
“…Bistable opsins are promising for optogenetic applications because they can be activated and inactivated with specific wavelengths of light, providing high temporal precision. For instance, JSR1 has been used as an optogenetic tool in zebrafish reticulospinal V2a neurons, where activation of JSR1 lead to an increase of Ca 2+ and evoked a change in swimming behaviour [44]. The main issue with using JSR1 as an optogenetic tool is that the λ max of the active and inactive states overlap, meaning that there will be a mixture of active and inactive states upon illumination and the activity of JSR1 cannot be controlled precisely [16].…”
Section: Discussionmentioning
confidence: 99%
“…They are therefore classified as ‘bistable’ due to the thermal stability of the PSB in both the inactive and active states. Bistable opsins are potential optogenetic switches to control G protein signaling pathways, and in vivo studies have demonstrated the capability of JSR1 as an optogenetic tool to manipulate neuronal signaling in animals (5).…”
Section: Introductionmentioning
confidence: 99%